Suitability of Ontario‐Grown Hard and Soft Wheat Flour Blends for Noodle Making. Issue 5 (15th September 2014) - Lu, Zhanhui; Seetharaman, Koushik
ABSTRACT: This study evaluated the blending of flours made from an Ontario hard red winter wheat (HWF) and an Ontario soft red winter wheat (SWF) and compared it with a commercial standard noodle flour (control) made from Canadian Western Hard Red Spring wheat to assess the impact on white salted noodle‐making performance and texture of cooked noodles. Flour characteristics, gluten aggregation, and starch pasting properties were assessed with a farinograph, GlutoPeak tester, and Rapid Visco Analyzer, respectively. The machinability of dough was evaluated with an SMS/Kieffer rig attached to a TA.XT Plus texture analyzer. Tensile and bite tests of cooked noodles were also conducted. Blending HWF with standard noodle flour decreased gluten strength and dough extensibility linearly proportional to the blend ratio, whereas a curvilinear response from blending SWF with standard noodle flour was observed. HWF demonstrated more favorable pasting properties except for lower peak viscosity for noodle making than standard noodle flour. Below a 20% blend ratio with HWF, no significant changes were seen on dough extensibility, cooking loss, tensile properties, and bite testing parameters of cooked noodles. It can be concluded that blending HWF up to a 20% level caused no significant change in the processing properties of dough and cooked noodle quality. The results also showed that the GlutoPeak tester is a sensitive tool for evaluating gluten strength in wheat flour.